Aggression and violence in adolescents in the iberoamerican context, a systematic review - Javela, José Julián (2022)
This research is a systematic review that uses the Prism method, searching different databases to systematically analyze studies related to aggression and violence in adolescents in Iberoamerica. Objective: The present study aims to systematically analyze studies related to aggression and violence in adolescents in Iberoamerica. Method: Research works were collected from a total of 5 databases. For the selection of the articles, keywords or search terms were entered, and inclusion and exclusion criteria were applied. After the complete reading, a total of 47 research studies were selected. Results: The country retrieved with the largest number of articles was Brazil with a total of 11 documents, followed by Spain with ten, and the United States with a total of eight documents. It was also found that the database with the largest number of articles retrieved was Scopus, with 21 papers equivalent to 44.7 % of the total documents retrieved, followed by Science Direct and SciELO, each with a percentage of 19.1 %, equivalent to 9 documents.